Forecast and analysis of the Portuguese car fleet and automotive aftermarket using time-series modelling - Pires, João Miguel Nascimento Oliveira Sancho (2022)
The car fleet size and composition have a direct impact on the automotive aftermarket business value. This study used Time-series models to forecast the Portuguese car fleet composition until2030,whichis projected to rise by just2%(6.3 million vehicles). It is highlighted the exponential growth of EVs reaching a 12.2% fleet share by2030,under a Neutral scenario. The car fleet composition was adjusted under three scenarios after external conditioning variables such as environmental policies and the introduction of shared cars were factored in, affecting the automotive aftermarket value. While it is expected to increase from 914.2to 950.7 million euros between 2018and 2030, the maintenance market share of internal combustion engine vehicles is expected to decrease. On the other hand, next-generation vehicles such as EVs, shared cars, and partially automated cars, are projected to take a growing share of the car fleet and automotive after market value of the future.